Analisis Dampak Indeks Kemiskinan dan Pendidikan Terhadap Pertumbuhan Ekonomi Provinsi Jawa Barat Tahun 2017 Sampai Dengan Tahun 2022 - Rahman, Muhammad Arif; Dewi, Murtisari; Sopiyanti, Siti; Yulianti, Fina Olivia; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Poverty is a situation where individuals or groups are unable to meet their basic needs to maintain and improve a dignified life. The education index has a significant relationship with economic growth. Poverty can negatively impact economic growth, as it can hinder people's access to quality education. Over a specified period, economic growth reflects continuous changes in a country's economic conditions towards a more sustainable and improved state. The method used in this research is the descriptive method. From the significant correlation results (Sig.(2-tailed)), the probability figure for GDP is 0 > 0.05, for Poverty (X1) the probability is 0.939 > 0.05 which correlates with GDP (Y), and for the Education Index (X2) the probability is 0.637 > 0.05 which also correlates with GDP (Y). This indicates that there is a significant correlation between poverty and the education index with economic growth.